1970
DOI: 10.3329/bjch.v34i1.5695
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Hepatic Function: Helpful to Diagnose and Assess Severity of Perinatal Asphyxia

Abstract: Background and Objectives: Diagnosis of perinatal asphyxia is mostly establishedretrospectively. But it is difficult to diagnose perinatal asphyxia retrospectively in theabsence of perinatal records. As because of hypoxaemia, different organ systems ofthe body are affected in perinatal asphyxia, this study was done to assess the hepaticfunction for the diagnosis of perinatal asphyxia and to find out any correlation existingbetween hepatic enzyme change and the severity of perinatal asphyxia.Methods: A total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
6
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 14 publications
11
6
1
Order By: Relevance
“…In the present work, we observed significantly lower values of total protein and serum albumin in asphyxiated neonates and that they correlate poorly with the severity of birth asphyxia as assessed by HIE stage and Apgar score. Islam et al 11 reported mean total protein and serum albumin similar to our study in asphyxiated neonates. The prevalence of hypoproteinemia noted by Godambe and coworkers 16 was 34% in asphyxiated newborns.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In the present work, we observed significantly lower values of total protein and serum albumin in asphyxiated neonates and that they correlate poorly with the severity of birth asphyxia as assessed by HIE stage and Apgar score. Islam et al 11 reported mean total protein and serum albumin similar to our study in asphyxiated neonates. The prevalence of hypoproteinemia noted by Godambe and coworkers 16 was 34% in asphyxiated newborns.…”
Section: Discussionsupporting
confidence: 90%
“…The present work demonstrated that serum ALP increased more than the command group, and the differences were statistically significant, but significant correlation with stages of HIE was not established. Islam et al 11 reported mean ALP similar to our study in asphyxiated neonates, but showed significant correlation with stages of HIE.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This was similar to the results of the work done by Islam et al in 2010. 15 This was likely due to the fact that with increasing severity of hypoxic-ischemic injury, more of the enzymes were being released from the damaged cells. In contrary, Choudhary et al 22 reported no correlation between the levels of the enzymes and severity of PA using the Apgar scores.…”
Section: Discussionmentioning
confidence: 99%
“…There is need for biomarkers that can define the presence and severity of asphyxia in babies with severe PA, especially when the labor is not supervised by skilled personnel. Consequently, several studies [13][14][15][16] have been undertaken to determine the relationship between intracellular enzymes and PA. There is dearth of data in Nigeria, one of the major countries where PA is a major problem.…”
Section: Introductionmentioning
confidence: 99%